Fermentation of Carrot Juice by Probiotics: Viability and Preservation of Adhesion (International Journal of Biotechnology for Wellness Industries, 2013)
In the present work, carrot juice was investigated as an alternative carrier for probiotics. Pasteurized juice was fermented anaerobically over night at 37oC with selected probiotics and their viability was assessed after 1, 2, 4, 8 and 12 week storage. Identification was performed by species specific PCR. Mucus adhesion was assessed of carrot juice and laboratory medium grown Lactobacillus strains. At inoculation, the probiotic strains were present at levels of 106-107 CFU/ml and during fermentation the lactobacilli numbers increased to 109-1010 CFU/ml. After four weeks storage, Lactobacillus levels remained almost unchanged and after 12 weeks there were still 107-109 CFU/ml lactobacilli. Bifidobacteria, however, did not grow and started to decline after two weeks and were undetectable after 8 weeks. Adhesion of carrot juice grown lactobacilli was 50-70% less then adhesion of the strains grown in laboratory medium. The results suggest that fermented carrot juice is a promising carrier for probiotic lactobacilli but not bifidobacteria, but may alter the phenotypic properties of lactobacilli.